(untitled) (Third Sector Social Economic Review, 2023)
In general, a financial investment portfolio is created taking into account the risk and return expectations of investors. The best business portfolio creation process can be called portfolio management. The greatest capital of an investor is to prepare a good portfolio. In this study, the literature uses fuzzy logic in the field of Finance Hiroshi Konno and Hiroaki Yamazaki (1991) model is used, whether the BIST Banking Index (XBANK) ten banks in the stocks of 02 January 2021 – December 31, 2021, using the modeling of monthly closing prices between the period reviewed. The model created in the study was analyzed with the help of the WinQSB v.1.0 package program. According to the solution results; The best portfolio includes four bank stocks AKBNK, GARAN, ISCTR and YKBNK, with expected return blurred by 0.52. In this model, the smallest risk ratio was 1.834. The objective function value reached by blurring the expected rate of return to 1.02 was 1.246.